Declaration of conflict of interest in medical researchers: A cross‐sectional study from China. Issue 2 (31st August 2021) - Yang, Lili; Xu, Siyun; Shao, Jufang; Wang, Panzhi; Wang, Xianjun; Qi, Qi; Yang, Rongwang
Abstract: Conflict of interest (COI) declaration policies are not commonplace in China and the level of awareness and reporting among Chinese researchers have not been fully investigated. This study sought to discover the presence of COI policies in high‐impact Chinese journals, the compliance of authors with these policies and the awareness of authors with the principles of COI and to compare these findings against comparable international journals. The study included review of publications and policies and a survey of Chinese researchers. It compared 14 Chinese journals and 16 international journals during 2018. Most Chinese journals have a COI policy, but only 0.6% of articles published in 2018 included a statement of potential COI. All international journals required COI statements in all articles, and 15.6% of Chinese articles declared a potential COI (of which most were financial COIs). However, this was lower than COI declarations from non‐Chinese authors (47.8%). When surveyed, 24% of researchers had potential COI in a submitted article, but only 4.2% declared a COI: most of the under‐declaration was due to lack of knowledge about COI, followed by concern that a COI would lead to rejection of their articles. The research shows that there is a knowledge and policy gap in China that needs to be rectified and that international journals can be used as a reference point for good practice.